Consumers’ acceptance towards mass-customization of bungalows design. a study of Noris Ventures Sdn. Bhd. / Siti Aishah Abdul Manaf - Abdul Manaf, Siti Aishah (2010)
The purpose of this research is to study the consumer acceptance toward mass-customization of bungalows design at Noris Ventures Sdn. Bhd. in term of consumer’s knowledge, consumer’s attitude and consumer’s service by Noris Ventures. Therefore the objective of this research is first to analyse the relationship between consumer’s knowledge and consumer acceptance. Second is to analyse the relationship between consumer’s attitude and consumer acceptance. Lastly is to analyse the relationship between consumer’s service by Noris Ventures and consumer acceptance. In this study, we used interview and questionnaire to identify the relevant aspect regarding the study on the consumer acceptance toward mass-customization of bungalows design and the other secondary sources such as report, database and so on for data collection. Based on frequency, correlations test and regression test, a clear finding and result are observed. The findings showed the most customers were agreed the consumer acceptance is important to attract the customer to buy the product. From this study, the researcher has identified that the consumer’s (knowledge and attitude) influence services by Noris Ventures Sdn. Bhd. The results prove by the correlations and regression analysis. The research is also able to give some recommendation and suggestions on how to improve and increase the consumer acceptance after the analysis, finding and interpretation were made.